A Taxonomic Study of Noctuinae Subfamily (Lepidoptera, Noctuidae) in Isfahan Province - Asghar Shirvani; Maryam Rashki (تاکسونومی و بیوسیستماتیک, 2019)
Abstract Iran, in terms of biogeography, has considerable diversity. Considering the importance of conducting faunistic and taxonomic investigations and identifying the fauna of insects in different climates of the country, in this study, which was conducted to identify and examine the taxonomy of the subfamily Noctuinae in Isfahan province during the years 2011 and 2012, moth specimens were collected by light traps from different geographic regions. The collected specimens were then transported to the laboratory and pinned, and slides were prepared from their genitals.  The samples were identified with the help of reliable scientific sources. Among the 22 collected species and subspecies belonging to this subfamily, 17 species and subspecies belonging to eight genera were reported for the first time in Isfahan province. Taxonomic characters of the species and subspecies and their distribution and biological information as well as the image of whole insects are presented.